Electrochemical swelling induced high material utilization of porous polymers in magnesium electrolytes. (May 2022) - Wang, Xiaojun; Dong, Hui; Eddine Lakraychi, Alae; Zhang, Ye; Yang, Xu; Zheng, Hongzhi; Han, Xinpeng; Shan, Xiaonan; He, Chuanxin; Yao, Yan
Graphical abstract: Abstract: Magnesium rechargeable batteries are promising candidates for large-scale energy storage due to their -high safety, low material cost, and earthabundant materials. Many redox-active polymers have recently been reported to show excellent cycling stability with decent Mg-storage performance. However, compared to their Li counterparts, these polymers exhibit lower Mg-storage capacity, resulting in a low ratio of materials utilization ( η Mg/ η Li) for the same polymer in two electrolyte systems (i.e., Mg vs. Li electrolytes). Herein, we present a sulfur-linked porous polymer, poly(hexaazatrinaphthalene sulfide) (PSHATN), which sets a record for material utilization of 98% among all polymer electrodes and delivers a reversible capacity of 196 mAh g −1 in Mg electrolytes. Based on electrochemical impedance spectroscopy and operando optical microscopy, we discover a strong correlation between specific capacity and degree of electrochemical swelling of polymers in both electrolytes. Importantly, the high ratio ( η Mg/ η Li ) of PSHATN is ascribed to sufficient electrochemical swelling due to its large pore volume and flexible polymer nature, in contrast to linear polymers and rigid covalent organic frameworks that swell less effectively. This work highlights the critical need for polymer swelling in promoting ion transport in redox polymers for high material utilization and offers important polymer structural design insights for multivalent ion-based energy storage.